Blue ocean leadership and employee engagement - Hanafi W.N.W.; Daud S.; Islam M.K.; Bahrin N.L.; Ramli A.A.; Isa A. (American Scientific Publishers, 2023)
Due to the globalization, rapid changing workplace, and provocative technological era, business organizations are facing enormous challenges internally and externally in this presence and fierce competitive environment. Leaders need to play the crucial role for accepting and overcoming those stated challenges to survive with competitive market positions. Hence, blue ocean leadership (BOL) focuses on what leaders need to do, not on who they need to be, which is far easier to change and has a direct impact on performance. The main purpose of this study is to identify the blue ocean leadership attributes those were practiced in the organization and examine the relationship towards the employee engagement. This study surveyed 329 respondents who were holding manager and above positions at few Governments Linked Companies (GLCs) and Multi-National Companies (MNCs) in Malaysia. The findings of this study are expected to contribute to the new dimension of leadership, and therefore, leaders will be able to know the leadership attributes which could help an organization to increase its leadership strength quickly and ensuring high performance of the business by achieving the organizational goals and objectives effectively. 2017 American Scientific Publishers. All rights reserved.